SELF-EFFICACY, SOCIAL CAPITAL, AND ENTREPRENEURIAL INTENTION AMONG RETURNEE MIGRANT WORKERS: A PATH ANALYSIS APPROACH - Fatwa Zuhanea (JURNAL ILMIAH EDUNOMIKA, 2022)
The reintegration of returnee migrant workers into domestic labor markets poses significant socioeconomic challenges for labor-sending countries including Indonesia. Entrepreneurship represents a pivotal reintegration pathway, yet the psychological and social antecedents of entrepreneurial intention in this population remain underexplored. This study investigates the influence of self-efficacy and social capital on entrepreneurial intention among returnee migrant workers (Tenaga Kerja Indonesia Purna/TKI Purna) in Cilacap Regency, Central Java, using a path analysis approach. Grounded in Social Cognitive Theory (Bandura, 1986) and Bourdieu's (1986) Social Capital Theory, this study collected data from 145 returnee migrant workers through stratified random sampling. Path analysis using AMOS 24.0 revealed that self-efficacy significantly and positively influenced entrepreneurial intention (β = 0.412, p < 0.001), social capital significantly influenced entrepreneurial intention (β = 0.338, p < 0.001), and self-efficacy significantly influenced social capital (β = 0.521, p < 0.001). Social capital partially mediated the relationship between self-efficacy and entrepreneurial intention (indirect effect β = 0.176, p = 0.003). The R² for entrepreneurial intention was 0.587. These findings have significant implications for reintegration policy design and post-migration entrepreneurship support programs. Keywords: self-efficacy, social capital, entrepreneurial intention, returnee migrant workers, TKI Purna, path analysis